Toner manufacturing method
By integrating ultra-fine bubbles into the toner manufacturing process, the method addresses the challenges of pigment dispersibility and particle size reduction, resulting in toners with improved coloring power and pulverization efficiency.
Patent Information
- Application Number
- JP2023112858
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
AI Technical Summary
Existing toner manufacturing methods face challenges in achieving high pigment dispersibility and particle size reduction without compromising productivity, as conventional techniques either fail to achieve sufficient hiding rates or leave behind residual grinding aids that affect toner performance.
Incorporating ultra-fine bubbles (UFB) with particle sizes of 1000 nm or less into the toner mixture during melt-kneading to enhance dispersibility of pigments and release agents, utilizing their crushing and surfactant effects to improve dispersibility and pulverization efficiency without residual aids.
The method enables the production of toners with enhanced coloring power and improved pulverization properties, achieving finer particle sizes while maintaining productivity and avoiding residual grinding aids.
Smart Images

Figure 2025010720000006 
Figure 2025010720000001 
Figure 2025010720000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a toner used in an electrophotographic system, an electrostatic recording system, an electrostatic printing system, and a toner jet system. [Background technology]
[0002] In recent years, full-color electrophotographic multifunction machines have become widespread, and are increasingly being applied to the printing market. In the printing market, there is a growing demand for high speed, high image quality, high productivity, and low running costs while being compatible with a wide range of media (paper types). In toner, coloring power can be improved by improving the dispersibility of colorants in the toner, and image quality can be improved by further reducing the particle size of the toner.
[0003] A melt-kneading and pulverizing method is known as a general method for producing toner particles. Specifically, this method involves melting and kneading toner constituent materials such as binder resin, colorant, and release agent, cooling and solidifying the mixture, and then pulverizing the mixture to obtain toner particles. Thereafter, the mixture is classified to a desired particle size distribution and external additives such as a fluidizing agent are added as necessary to produce the toner.
[0004] In order to increase the coloring power of a toner, for example, Patent Documents 1 to 3 propose a technique of dispersing the pigment by kneading a resin, water, and a pigment in a melt-kneading step in the toner production process, thereby improving color reproducibility / coloring power. On the other hand, in order to reduce the particle size of the toner, it is necessary to make the kneaded material finer in the process of pulverizing it, but since there is a concern that the finer the pulverization, the lower the productivity, there is a demand for highly efficient pulverizing means and devices to maintain production volume and reduce energy consumption. Patent documents 4 and 5 propose adding a pulverizing aid to the toner kneaded material as a means of making the toner kneaded material easier to pulverize and thereby improving pulverization efficiency without investing in production equipment. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2005-352131 A [Patent Document 2] JP 2003-098739 A [Patent Document 3] JP 2002-072554 A [Patent Document 4] JP 2008-191491 A [Patent Document 5] JP 2015-132645 A Summary of the Invention [Problem to be solved by the invention]
[0006] In order to improve coloring power, it is effective to increase the hiding rate of the medium by a colorant such as a pigment, but the pigment dispersibility in the toner particles described in the above Patent Documents 1 to 3 is not sufficient to obtain a high hiding rate, and there is room for improvement. Therefore, a technology is required to finely disperse dispersed substances such as pigments in a binder resin to a higher degree. Also, as described in Patent Documents 4 and 5, a method of making the toner particle size smaller by adding inorganic fine particles or the like to a kneaded toner material as a grinding aid and finely grinding the toner is known. However, the grinding aid may remain in the toner and affect the toner performance, and therefore, when it is desired to make only the particle size smaller in a toner with an existing formulation, the grinding aid cannot be used.
[0007] The present disclosure is directed to a method for producing a toner capable of finely dispersing a dispersed substance in a binder resin to a higher degree. The present invention is directed to a method for producing a toner that can improve the toner grindability without leaving any residue of a grinding aid or the like. [Means for solving the problem]
[0008] The present disclosure provides a method for producing a toner, comprising: The method for producing the toner includes the steps of: The method includes a melt-kneading step of melt-kneading a mixture A containing a binder resin and a substance to be dispersed in the binder resin to obtain a kneaded product, the mixture A contains 1.0 to 10.0 parts by mass of water relative to 100.0 parts by mass of the binder resin and the dispersed substance in total, The water contained in the mixture A contains bubbles including ultrafine bubbles having a particle diameter of 1000 nm or less, The water contained in the mixture A has ultra-fine bubbles of 1.0×10 4 The present invention relates to a method for producing a toner containing more than 1000 particles / mL. Effect of the Invention
[0009] According to the present disclosure, it is possible to provide a method for producing a toner that can finely disperse a dispersed substance in a binder resin to a higher degree. For example, the present disclosure can provide a method for producing a toner that has excellent coloring power and a method for producing a toner that can improve the toner grindability without leaving any residue of a grinding aid or the like. [Brief description of the drawings]
[0010] [Figure 1] Schematic diagram of a mechanical crusher DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined.
[0012] The present disclosure provides a method for producing a toner, comprising: The method for producing the toner includes the steps of: The method includes a melt-kneading step of melt-kneading a mixture A containing a binder resin and a substance to be dispersed in the binder resin to obtain a kneaded product, the mixture A contains 1.0 to 10.0 parts by mass of water relative to 100.0 parts by mass of the binder resin and the dispersed substance in total, The water contained in the mixture A contains bubbles including ultrafine bubbles having a particle diameter of 1000 nm or less, The water contained in the mixture A has ultra-fine bubbles of 1.0×10 4 The present invention relates to a method for producing a toner containing more than 1000 particles / mL.
[0013] The above-mentioned toner manufacturing method allows the dispersed material to be finely dispersed in the binder resin to a higher degree. Therefore, for example, a method for manufacturing a toner having excellent coloring power can be provided. In addition, for example, a method for manufacturing a toner that improves toner grindability without leaving any residue of a grinding aid can be provided. The present inventors consider the reason for this to be as follows.
[0014] Conventionally, when melt-kneading is performed using a thermal kneader such as a pressure kneader or a continuous extruder, the mixture of toner constituent materials such as binder resin, pigment as a colorant, and release agent is gradually heated by the heat of the kneader while being mixed with each other by the shear of the device to become a kneaded product. At this time, the pigment, which is the dispersed material in the binder resin, is subjected to a secondary shear of the device. The particles are crushed, and the release agent to be dispersed is also broken down by the shearing force of the device, so that it is finely dispersed in the kneaded material.
[0015] In the present disclosure, when melt-kneading is performed, water containing bubbles including ultrafine bubbles (UFB) (hereinafter also referred to as "UFB water") is added to mixture A, which is a mixture of raw materials containing a binder resin and a substance to be dispersed in the binder resin. By adding UFB water to mixture A, it becomes possible to finely disperse the substance to be dispersed in the binder resin to a higher degree than when UFB water is not added. UFB are bubbles with a size of, for example, several tens of nm to about 1 μm (1000 nm), which do not rise to the surface in water and can remain stable for a long time.
[0016] The following mechanism is assumed to enable the inclusion of UFB water in mixture A to achieve a high degree of fine dispersion of the dispersed material during melt kneading. The UFB present in water has a collapsing effect and a surface-active effect. The collapsing effect is that when an external physical force is applied, the bubbles contract, causing the pressure inside the bubbles to rise rapidly, and generating a shock wave when the bubbles disappear. When UFB water is mixed into the raw material mixture A, the surface-active effect causes the UFB to adsorb to the binder resin and the surface of the dispersed material. Furthermore, the shock waves generated by the UFB collapsing due to shear during kneading can apply an even stronger external force to the dispersed material than with conventional kneading, and it is believed that the dispersed material can be finely divided and finely dispersed with high efficiency.
[0017] In the case where, for example, a pigment is contained as the dispersed substance, it is considered that the pigment is more finely dispersed in the toner and the concealing rate against light is improved, thereby improving the color development and coloring properties. Therefore, it is preferable that the dispersed substance contains a pigment.
[0018] In addition, when a release agent is contained as the dispersed substance, the release agent is more finely dispersed in the kneaded mixture of the toner constituent materials. The part of the kneaded mixture where the release agent is present is likely to become a cut surface during pulverization, so that the pulverization efficiency is improved in the pulverization step after kneading. Therefore, the toner pulverization property can be improved without leaving any residue of a pulverization aid. Therefore, it is preferable that the dispersed substance contains a release agent.
[0019] In addition, when the dispersed substance contains, for example, a pigment and a release agent, the pigment is finely dispersed in the toner, thereby improving the coloring power, and the release agent is finely dispersed in the toner, thereby improving the toner grindability. Therefore, it is preferable that the dispersed substance contains a pigment and a release agent.
[0020] Based on the above mechanism, it is believed that the present disclosure can provide a toner manufacturing method capable of finely dispersing the dispersed substance in the binder resin to a higher degree. The dispersed substance is not limited to a pigment or a release agent, and may be any substance that can exert the above-mentioned crushing action and surface activity action. Examples of the dispersed substance include plasticizers, charge control agents, colorants other than pigments, resin particles and inorganic particles to be contained inside toner particles.
[0021] First, we will explain about ultra-fine bubble water (UFB water). <Ultra-fine bubbles> Bubbles with a particle size of 100 μm or more (submillimeter bubbles) rise in water and disappear at the air-liquid interface. Bubbles with a particle size of more than 1 μm but less than 100 μm (microbubbles) rise slower in water, but cannot withstand water pressure and are prone to disappear in water. In contrast, ultrafine bubbles (nanobubbles) with a particle size of 1 μm (1000 nm) or less can exist stably in water for several months. By including extremely fine bubbles such as these ultrafine bubbles in the mixture of raw materials used in the manufacture of toner or master batch, the dispersibility of the dispersed material can be improved due to the crushing effect and surface activity effect.
[0022] The bubbles are preferably composed of at least one gas selected from the group consisting of rare gases, oxygen gas, nitrogen gas, carbon dioxide, ozone gas, and air. Among them, at least one gas selected from the group consisting of oxygen gas, nitrogen gas, carbon dioxide, ozone gas, and air is preferable. In particular, it is preferable that the gas constituting the bubbles is air. In the case of air, this is preferable because no equipment (gas generator, storage equipment such as gas cylinder) accompanying the bubble generator is required.
[0023] In particular, mixture A, which is a mixture of raw materials for toner particles, needs to contain 1.0 to 10.0 parts by mass of water per 100.0 parts by mass of the binder resin and the dispersed substance in total. The water contained in mixture A is UFB water containing bubbles containing specific UFBs, which will be described later. If the amount of water containing ultra-fine bubbles is less than 1.0 part by mass, the liquid will not reach the surface of the raw materials sufficiently, so there will be fewer points of action for the crushing action, and the effect of dispersing the dispersed material may not be fully achieved.On the other hand, if the amount of water containing ultra-fine bubbles is more than 10.0 parts by mass, the amount of water present between the raw materials will be too much, making it difficult for the raw materials to be sufficiently sheared by the kneader, and the dispersion effect of the dispersed material will not be improved.
[0024] The content of the water is preferably 2.0 to 8.0 parts by mass relative to 100.0 parts by mass of the binder resin and the dispersed substance in total. In the toner manufacturing process, for example, when going through a master batch described later, the mixture of raw materials may be melt-kneaded several times. It is considered that the water contained is usually evaporated by performing melt-kneading. Therefore, when going through several melt-kneading steps, it is preferable to mix 1.0 to 10.0 parts by mass of UFB water with 100.0 parts by mass of the binder resin and the dispersed substance in the mixture in each melt-kneading step.
[0025] The water contained in mixture A contains bubbles including ultra-fine bubbles with a particle diameter of 1000 nm or less. The water contained in mixture A contains 1.0 x 10 ultra-fine bubbles with a particle diameter of 1000 nm or less. 4 It is necessary that the content is 1.0×10 4 If the number of bubbles is less than 1.0×10 / mL, the amount of UFB attached to the surface of the dispersed material is insufficient, and it is considered that the crushing effect or surface activity effect sufficient to disintegrate the dispersed material during melt kneading is not obtained. Therefore, it is considered that the dispersed material cannot be finely dispersed to a high degree. 4 Must be 5.0 x 10 cells / mL or more. 6 Preferably, the number is 1 / mL or more.
[0026] On the other hand, from the viewpoint of productivity, the number density of UFB is 3.0×10 10 The number density of UFB is preferably 1.0×10 4 ~3.0×1010 5.0×10 6 ~3.0×10 10 pieces / mL.
[0027] Furthermore, in the water contained in the mixture A, the number-average particle diameter of the bubbles is preferably 1000 nm or less. When the number-average particle diameter of the bubbles contained in the water is 1000 nm or less, the bubbles tend to be smaller than the diameter at which the bubbles perform Brownian motion, so that the bubbles tend to exist more stably. Therefore, the bubbles can be more sufficiently present during the time from mixing with the binder resin and the dispersed material until being put into the kneader. In addition, when the number-average particle diameter is within the above range, the number of contact points of the bubbles with the surface of the dispersed material increases, so that it is considered that a sufficient crushing effect or surface activity effect for disintegrating the dispersed material can be easily obtained. Therefore, it is considered that the dispersed material can be more easily finely dispersed to a higher degree.
[0028] For this reason, the number-average particle size of the bubbles contained in the water to be added is preferably 1000 nm or less, more preferably 700 nm or less. There is no particular lower limit to the particle size. The number-average particle size of the bubbles is, for example, preferably 10 to 1000 nm, more preferably 50 to 1000 nm, even more preferably 10 to 700 nm, and even more preferably 50 to 700 nm. The thickness is preferably from 100 to 700 nm.
[0029] The particle size and number density of UFBs are measured by a laser diffraction / scattering method. The particle size of air bubbles is the number-average particle size. The number density of UFBs is the ratio (pieces / mL) of air bubbles having a particle size equal to or smaller than a given value per volume of water. In the examples described below, the particle size of air bubbles was calculated using a nanoparticle size distribution measuring device (product name "SALD-7500nano", manufactured by Shimadzu Corporation). In addition, the number density of UFBs smaller than 1000 nm was calculated using a nanotracking particle size measurement device (product name "Nanosite NS300", manufactured by Malvern Panalytical), which can observe the number of particles by imaging the scattered light due to laser irradiation via a camera.
[0030] The means for producing water containing UFB is not particularly limited as long as it can produce water containing bubbles with the desired particle size and particle concentration, and any known method can be used. For example, water containing fine bubbles can be produced using known devices that generate water containing fine bubbles, such as the fine bubble generating nozzle described in JP 2014-104441 A; the fluid mixing device described in WO 2009 / 088085 A; etc. By appropriately setting the operating conditions of these devices, it is possible to obtain bubble-containing water in which the particle size distribution of the bubbles is controlled within a desired range.
[0031] In addition, for example, as described in JP 2019-42732 A, film boiling can be caused by applying thermal energy to a liquid to generate bubbles, thereby producing bubble-containing water. By appropriately setting the film boiling conditions, etc., it is possible to obtain bubble-containing water in which the particle size distribution of the bubbles is controlled within a desired range.
[0032] In addition, as described in JP 2022-144980 A, UFB water is placed under reduced pressure to partially remove the water, thereby concentrating the water containing UFB and adjusting the number density of the UFB. Furthermore, UFB may be produced using commercially available (for research use) bubble-containing water (for example, product names "High Density Ultrafine Bubbles" and "Ultra High Density Ultrafine Bubbles" (both manufactured by Nanox)). The obtained UFB is added to mixture A in the raw material mixing process before melt kneading to produce a master batch and a toner.
[0033] <Binding resin> The toner particles contain a binder resin. As the binder resin, a known polymer can be used, and specifically, for example, the following polymers can be used. Examples of the styrene copolymers include polystyrene, poly-p-chlorostyrene, polyvinyltoluene, and other homopolymers of styrene and its substitutes; styrene-p-chlorostyrene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-acrylic acid ester copolymers, styrene-methacrylic acid ester copolymers, styrene-α-methyl chloromethacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, and styrene-acrylonitrile-indene copolymers; polyvinyl chloride, phenolic resins, natural resin-modified phenolic resins, natural resin-modified maleic acid resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyester resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins, and petroleum-based resins. These resins may be used alone or in combination of two or more.
[0034] Among these, the amorphous polyester resin is preferable. The amorphous polyester resin is preferably a condensation polymer of a carboxylic acid component and an alcohol component. The alcohol component may be a known one. The carboxylic acid component preferably contains at least one selected from the group consisting of terephthalic acid and fumaric acid. The alcohol component preferably contains an alkylene oxide adduct of bisphenol A (the average number of moles added is preferably 1 to 5 mol). As the acid component, a trivalent carboxylic acid such as trimellitic acid may be used.
[0035] The binder resin may be a mixture of a low softening point polyester resin L and a high softening point polyester resin H. The content ratio (L / H) of the low softening point polyester resin L and the high softening point polyester resin H is, for example, 60 / 40 to 90 / 10 by mass. The softening point of the low softening point polyester resin L is preferably 70°C or higher and lower than 100°C. The softening point of the high softening point polyester resin H is preferably 100°C or higher and 160°C or lower.
[0036] The binder resin may contain a crystalline polyester resin from the viewpoint of achieving both low-temperature fixability and anti-blocking properties. The crystalline polyester resin is preferably a condensation polymer of an alcohol containing an aliphatic diol having 2 to 23 carbon atoms and a carboxylic acid containing an aliphatic dicarboxylic acid having 4 to 24 carbon atoms.
[0037] The crystalline polyester resin is more preferably a condensation polymer of an alcohol containing an aliphatic diol having 4 to 12 carbon atoms in an amount of 80 mol% to 100 mol% (more preferably, 85 mol% to 100 mol%) relative to the total alcohol constituting the crystalline polyester resin, and an aliphatic dicarboxylic acid having 4 to 20 carbon atoms in an amount of 80 mol% to 100 mol% (more preferably, 85 mol% to 100 mol%) relative to the total carboxylic acid constituting the crystalline polyester resin.
[0038] The aliphatic diol is preferably a straight-chain aliphatic diol, and examples thereof include 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, and derivatives thereof. The derivative is not particularly limited as long as it can obtain a similar resin structure by condensation polymerization. For example, the derivative obtained by esterifying the diol can be used.
[0039] The aliphatic dicarboxylic acid is preferably a straight-chain aliphatic dicarboxylic acid, and examples thereof include malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, glutaconic acid, azelaic acid, sebacic acid, hexadecanedioic acid, eicosanedioic acid, and derivatives thereof. The derivative is not particularly limited as long as it can obtain a similar resin structure by condensation polymerization. For example, examples include acid anhydrides of the dicarboxylic acids, and derivatives obtained by alkyl esterification or acid chloride of the dicarboxylic acid component. On the other hand, the carboxylic acid may be used in combination with a carboxylic acid other than the aliphatic dicarboxylic acid.
[0040] <Coloring agent> The toner particles may contain a colorant. That is, the dispersed material may contain a colorant, and it is preferable that the dispersed material contains a pigment. Usually, except for the case of producing a clear toner described later, the dispersed material contains a colorant such as a pigment. Examples of the pigment include known organic pigments, carbon black, and magnetic materials. Examples of cyan pigments include copper phthalocyanine compounds and their derivatives, anthraquinone compounds, basic dye lake compounds, etc. Specific examples include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, 66, etc. Examples of magenta pigments include condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds.Specific examples include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, 254, and CI Pigment Violet 19.
[0041] Examples of yellow pigments include condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 191, and 194. Examples of black pigments include carbon black, magnetic materials, and pigments toned to black using the above-mentioned yellow pigments, magenta pigments, and cyan pigments. Examples of white pigments include titanium oxide, magnesium oxide, aluminum oxide, zinc oxide, barium sulfate, calcium carbonate, calcium titanate, strontium titanate, silica, clay, and talc.
[0042] The pigments can be used alone or in combination of two or more. The colorants, which can also be used in the form of a solid solution, are preferably selected from the viewpoints of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility in toner particles.
[0043] The content of the colorant (pigment) in mixture A (or the first mixture or second mixture described below) is preferably 1 to 60 parts by mass, more preferably 1 to 20 parts by mass, and even more preferably 5 to 15 parts by mass, relative to 100 parts by mass of the binder resin. When producing a master batch described below, that is, when mixture A is the first mixture, the content of the colorant is preferably 20 to 60 parts by mass, more preferably 30 to 55 parts by mass, relative to 100 parts by mass of the binder resin. When the pigment is a cyan, magenta, yellow or black pigment, the content is preferably 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the binder resin. When the pigment is a white pigment, the content is preferably 20 parts by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the binder resin, from the viewpoint of concealing the color of the base to express a sufficient white color and making it unrecognizable.
[0044] An example of a toner that does not contain a pigment or colorant is a clear toner that is melted on a print medium to achieve a gloss finish. As mentioned above, the clear toner can be made smaller in particle size by adding a release agent to the toner.
[0045] <Release agent> The toner particles may contain a release agent. That is, the dispersed material may contain a release agent. Examples of the release agent include the following. Hydrocarbon waxes such as low molecular weight polyolefins (low molecular weight polyethylene, low molecular weight polypropylene), alkylene copolymers, ceresin, paraffin wax, microcrystalline wax, and Fischer-Tropsch wax; silicones with melting points; fatty acid amides such as oleic acid amide, erucic acid amide, ricinoleic acid amide, and stearic acid amide; ester waxes such as stearyl stearate; vegetable waxes such as carnauba wax, rice wax, candelilla wax, wood wax, and jojoba oil; animal waxes such as beeswax; mineral and petroleum waxes such as montan wax, ozokerite, and ester wax; and modified versions of these.
[0046] The release agent may be used alone or in combination of two or more. The release agent preferably contains a hydrocarbon wax. The melting point of the release agent is preferably 150°C or lower, more preferably 40°C or higher and 130°C or lower, and even more preferably 40°C or higher and 110°C or lower. The content of the release agent in mixture A (or the second mixture described below) is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, and even more preferably 5 to 15 parts by mass, relative to 100 parts by mass of the binder resin.
[0047] <Charge control agent> The toner may contain a charge control agent as necessary. Any known charge control agent may be used, but a metal compound of an aromatic carboxylic acid is particularly preferred, as it is colorless, can charge the toner quickly, and can stably maintain a constant charge amount. Examples of negative charge control agents include the following: metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.
[0048] Positive charge control agents include quaternary ammonium salts, polymeric compounds having the quaternary ammonium salts in their side chains, guanidine compounds, and imidazole compounds. The charge control agent may be added internally or externally to the toner particles. The amount of the charge control agent added is preferably 0.2 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0049] <Developer> The toner can be used as a one-component developer, but it is preferable to mix it with a magnetic carrier and use it as a two-component developer in order to further improve dot reproducibility. It is also preferable in that stable images can be obtained over a long period of time. As the magnetic carrier, the following known magnetic carriers can be used: surface-oxidized iron powder or unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, chromium, and rare earth elements, alloy particles thereof, oxide particles, magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state. When the toner is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio in this case is, in terms of the toner concentration in the two-component developer, preferably 2% by mass or more and 15% by mass or less, and more preferably 4% by mass or more and 13% by mass or less.
[0050] <Toner manufacturing method> The procedure for producing the toner will be described. The toner production method is not particularly limited as long as UFB water is contained in mixture A, which is a mixture containing a binder resin and substances to be dispersed in the binder resin, such as a colorant and a release agent, and the mixture A is melted and kneaded to obtain a kneaded product, and the toner production method is preferably provided with a pulverization step of pulverizing the kneaded product obtained in the melt and kneading step.
[0051] The toner production method may include, for example, a step of grinding the kneaded product to a desired particle size, and then adhering inorganic fine particles to the surface of the toner particles to impart fluidity, or a step of dispersing the toner in an aqueous medium and then heating the toner to adjust the circularity of the toner. The toner production method may also include a step of adjusting the circularity of the toner particles using a heat treatment device as disclosed in JP2013-20244A.
[0052] <Raw material mixing process> In the raw material mixing process, the binder resin and the material to be dispersed in the binder resin are weighed out in predetermined amounts, mixed, and mixed to obtain a mixture. The mixing device is not particularly limited, but examples include a Henschel mixer (manufactured by Nippon Coke Company), a Super Mixer (manufactured by Kawata Corporation), a Ribocone (manufactured by Okawara Manufacturing Co., Ltd.), a Nauta mixer, a Turbulizer, and a Cyclomix (manufactured by Hosokawa Micron Corporation), a Spiral Pin Mixer (manufactured by Pacific Machinery Works, Ltd.), and a Loedige mixer (manufactured by Matsubo Corporation).
[0053] <Addition of water containing ultrafine bubbles as air bubbles> The water containing ultra-fine bubbles may be added to the mixture together with the binder resin in the raw material mixing step, or water may be added to the mixture mixed in the raw material mixing step and then mixed uniformly again in a mixer, etc. The raw material mixture containing water containing ultra-fine bubbles is referred to as Mixture 1.
[0054] <Melting and kneading process and cooling process> The toner raw material including the mixture 1 is melt-kneaded, for example, by a twin-screw extruder. In the melt-kneading step, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous-type kneader can be used, and a single-screw or twin-screw extruder is preferred because of its advantage of being capable of continuous production. The melt-kneading temperature is preferably about 100 to 200°C.
[0055] <Crushing process> Furthermore, the kneaded product 1 obtained by melt-kneading the mixture 1 is rolled with a two-roll mill or the like after melt-kneading, and cooled through a cooling process in which it is cooled with water cooling or the like. Next, the kneaded product 1 after cooling is pulverized to a desired particle size in a pulverization process. For example, in the pulverization process, the kneaded product is first coarsely pulverized with a crusher, a hammer mill, a feather mill, or the like. Furthermore, a finely pulverized product is obtained by finely pulverizing the product using a mechanical pulverizer such as an Innomizer (manufactured by Hosokawa Micron Corporation), a Cryptron (manufactured by Kawasaki Heavy Industries, Ltd.), a Super Rotor (manufactured by Nisshin Engineering Co., Ltd.), or a Turbo Mill (manufactured by Turbo Kogyo Co., Ltd.).
[0056] For example, a mechanical pulverizer as shown in the schematic diagram of FIG. 1 may be used. When a predetermined amount of coarsely pulverized material (material to be pulverized) is fed into the powder supply port (powder inlet) 101 of the mechanical pulverizer shown in FIG. 1, the coarsely pulverized material that has passed through the spiral chamber 102 is introduced into the pulverization chamber, which is the gap between the rotor 103 and the stator 104. Then, the material is instantaneously pulverized by an impact generated between the rotor 103, which has a number of grooves on its surface and rotates at high speed around the rotating shaft 107 in the pulverization chamber, and the stator 104, which has a number of grooves on its surface. After that, the finely pulverized material is discharged from the powder outlet 106 via the rear chamber 105. The left side of FIG. 1 is a schematic diagram viewed from the cross section of DD'.
[0057] The mechanical crusher is equipped with a cold air generator 108 that supplies cold air into the device through a powder supply port 101 together with the coarsely crushed material to be crushed. The mechanical crusher also includes a cold water supply port 109 and a cold water outlet 110 for passing water through a cooling jacket that controls the temperature of the device with cold water.
[0058] <Classification process> The classification step is a step in which the finely pulverized product obtained in the above-mentioned pulverization step is classified to obtain toner particles having a desired particle size distribution. As a classifier used for classification, known devices such as a wind classifier, an inertial classifier, and a sieve classifier can be used. Specifically, Classeal, Micron Classifier, and Spedic Classifier (manufactured by Seishin Enterprise Co., Ltd.); Turbo Classifier (manufactured by Nisshin Engineering Co., Ltd.); Micron Separator, Turbo Flex (ATP), and TSP Separator (manufactured by Hosokawa Micron Corporation); Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.); and De Examples of suitable separators include Dispersion Separator (manufactured by Nippon Pneumatic Mfg. Co., Ltd.); and YM Microcut (manufactured by Yaskawa Shoji Co., Ltd.).
[0059] The toner particles produced through the above steps may be used as they are as a toner. If necessary, inorganic fine particles such as silica, alumina, titania, etc., or resin fine particles such as vinyl resin, polyester resin, and silicone resin may be added to the toner particles by applying a shear force in a dry state to produce a toner. These inorganic fine particles and resin fine particles function as external additives such as a flowability aid and a cleaning aid.
[0060] The toner manufacturing method may include a step of melt-kneading the pigment with a part of the binder resin, for example, using a twin-screw extruder, applying shear stress to the pigment aggregates, and wetting the pigment particle surfaces with the binder resin. This step makes it possible to manufacture a pigment dispersion (master batch) in which the pigment is dispersed in advance in a part of the binder resin. The toner can then be manufactured through a dilution and kneading step in which the obtained pigment dispersion is melt-kneaded with the remaining binder resin and, if necessary, other materials to dilute it to a predetermined pigment concentration.
[0061] When a toner is manufactured through the above-mentioned master batch, the pigment dispersion may have insufficient pigment dispersibility, and coarse pigment particles of about several μm to 10 μm may be present. The coarse pigment particles in the pigment dispersion may not be completely disintegrated even in the next dilution melt kneading process, and may remain in the toner. If low resistance components such as coarse pigment particles are present in the toner or on the surface of the toner, charge leakage from the charged toner may progress, and the charge amount may decrease, causing toner scattering. Therefore, there is a demand for improving the pigment dispersibility in the pigment dispersion more than before and reducing the coarse pigment particles.
[0062] Even when the masterbatch is produced as described above, it is preferable to add UFB water to the mixture when producing the masterbatch by melt kneading, which is believed to provide the above-mentioned crushing and surface-active effects and to allow the pigment coarse particles to be disintegrated satisfactorily. That is, it is preferable that the melt-kneading step is a first melt-kneading step in which a first mixture containing a part of the binder resin and at least a part of the pigment is melt-kneaded to obtain a first kneaded product, and the first mixture is the above-mentioned mixture A. The toner production method further includes, after the first melt-kneading step, a second melt-kneading step in which a second mixture containing at least the first kneaded product and the remaining binder resin is melt-kneaded to obtain a second kneaded product.
[0063] It is preferable to also contain UFB water in the second mixture, i.e., the mixture of raw materials when the remaining binder resin and other materials as necessary are melt-kneaded using the master batch. In the second melt-kneading, the UFB water can also disperse the dispersed material well. The UFB water used here can be the same as that contained in the mixture A described above. Therefore, the second mixture contains 1.0 to 10.0 parts by mass of water with respect to 100.0 parts by mass of the binder resin and the dispersed material in the second mixture in total, The water contained in the second mixture contains bubbles including ultrafine bubbles having a particle diameter of 1000 nm or less, The water contained in the second mixture contains 1.0×10 ultra-fine bubbles with a particle diameter of 1000 nm or less. 4It is preferable that the content is 1 / mL or more. In the second mixture as well, the number average particle size of the air bubbles contained in the water is preferably in the above-mentioned range.
[0064] The weight average particle diameter (D4) of the toner is preferably from 3.0 μm to 20.0 μm, and more preferably from 4.0 to 10.0 μm.
[0065] In mixture A (or the first mixture or the second mixture described below), the content of the dispersed substance The ratio (water / substance to be dispersed) of the content of water (UFB water) based on the mass standard to the amount of the dispersed substance is not particularly limited. The ratio (water / substance to be dispersed) is preferably 0.02 to 1.00, and more preferably 0.03 to 0.90. If it is within the above range, the dispersibility of the dispersed substance can be improved.
[0066] <Method of measuring weight-average particle size (D4) of finely pulverized material and toner> The weight average particle size (D4) of the finely pulverized material and toner (hereinafter, simply referred to as toner in this measurement method) is measured with a precision particle size distribution measurement device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 50 μm aperture tube, and the accompanying dedicated software for setting measurement conditions and analyzing measurement data, "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), with an effective measurement channel count of 25,000, and the measurement data is analyzed and calculated. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter). Before carrying out the measurements and analyses, the dedicated software is set up as follows. In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 1 μm or more and 30 μm or less.
[0067] The specific measurement method is as follows. (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) Approximately 30 ml of the above-mentioned aqueous electrolyte solution is placed in a 100 ml flat-bottom glass beaker, and approximately 0.3 ml of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, with a pH of 7, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water is added as a dispersant. (3) A predetermined amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the Conaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, the electrolytic solution (5) in which the toner is dispersed is dropped into the round-bottom beaker (1) placed in the sample stand, and the measurement concentration is adjusted to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software provided with the device to obtain the weight average particle size (D4). When the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle diameter (D4). EXAMPLES
[0068] The present disclosure will be described in more detail below using examples and comparative examples, but these are not intended to limit the present disclosure in any way.
[0069] <Measurement of number-average particle size of bubbles and number density of UFB> The number average particle size of the bubbles and the number density of the UFBs were measured as follows. Using a particle size distribution measuring device (product name "SALD-7500nano", manufactured by Shimadzu Corporation), the average particle size of bubbles in the prepared UFB water was measured on a number basis. At this time, the SALD-7500nano batch cell (SALD-BC75) connected to the measuring device was filled with UFB water, and the refractive index value of the particles was set to 1.25-0.00i (i is a complex number). Analysis was performed using the attached software (WingSALDII), and the number-average particle size in the measurement range of 10 nm to 3000 nm was calculated.
[0070] In addition, the number density of UFBs of 1000 nm or less was calculated using a nanotracking particle size measurement device (product name "Nanosight NS300", manufactured by Malvern Panalytical). UFB water was loaded into the sample chamber of the Nanosight unit, and a video was recorded for 60 seconds at a frame rate of 25 fps. The particle movement was analyzed using the accompanying software (NTA software version 3.2) to calculate the number density (pieces / mL) of bubbles of 10 nm to 1000 nm. For UFB water 1 and 2 described later, the number density was determined by multiplying the number density of a solution diluted 100 times with pure water.
[0071] <Preparation of ultra-fine bubble water> UFB water was prepared by the following method: Table 1 shows the UFB water used in the examples and comparative examples.
[0072] (UFB Water 1) UFB water 1 is commercially available (for research use) UFB water (product name "High Density Ultra Fine Bubble", manufactured by Nanox).
[0073] (UFB Water 2~4) Each was diluted with 1 part UFB water and evaporated on a rotary evaporator (N-1300E-W The number density of the UFB was adjusted to the values in Table 1 by concentrating under reduced pressure using a Tokyo Rikakikai (Tokyo Rikakikai Co., Ltd.), and UFB water 2 to 4 were obtained.
[0074] (UFB Water 5) Using a micro-nano bubble generator (OM4-MDG-05, manufactured by Auratec), air bubbles were added to pure water at 25°C and 1.8 L / min for 5 passes, and the water was left to stand for 10 hours (this constitutes one cycle). After repeating this process 5 times, the water was diluted with pure water to adjust the number density of the UFB contained, and UFB water 5 was obtained.
[0075] (UFB Water 6 and 7) UFB water 6 was prepared in the same manner as UFB water 5, except that the number of cycles was 1. Furthermore, UFB water 7 was obtained by adjusting the number density of the UFB contained by diluting UFB water 6 with pure water.
[0076] (UFB Water 8) Using a micro / nano bubble generator (OM4-MDG-05, manufactured by Auratec), air bubbles were added to pure water at 25°C and 1.2 L / min for one pass. The number density of the UFB contained was adjusted by diluting the water with pure water to obtain UFB water 8.
[0077] [Table 1] In the table, the particle size indicates the number-average particle size of the bubbles.
[0078] <Production example of binder resin L> Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane: 72.0 parts by mass (0.20 parts by mole) Terephthalic acid: 28.0 parts by weight (0.17 parts by mole) Tin 2-ethylhexanoate (esterification catalyst): 0.5 parts by mass The above materials were weighed and placed in a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. Next, the atmosphere in the flask was replaced with nitrogen gas, and the temperature was gradually raised with stirring, and the reaction was carried out for 3 hours at a temperature of 200°C with stirring.
[0079] The pressure inside the reaction vessel was then reduced to 8.3 kPa and maintained for 1 hour, after which the vessel was cooled to 180° C. and returned to atmospheric pressure. Trimellitic anhydride: 1.3 parts by weight (0.01 parts by mole) tert-Butylcatechol (polymerization inhibitor): 0.1 parts by mass Thereafter, the above materials were added, the pressure in the reaction tank was reduced to 8.3 kPa, and the reaction was carried out for 1 hour while maintaining the temperature at 180°C. After confirming that the softening point measured according to ASTM D36-86 reached 85°C, the temperature was reduced to stop the reaction, and binder resin L was obtained.
[0080] <Production example of binder resin H> Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane: 72.3 parts by mass (0.20 moles; 100.0 mol% based on the total number of moles of polyhydric alcohol) Terephthalic acid: 18.3 parts by mass (0.11 moles; 65.0 mol% based on the total number of moles of polycarboxylic acids) Fumaric acid: 2.9 parts by mass (0.03 moles; 15.0 mol% based on the total number of moles of polycarboxylic acids) Tin 2-ethylhexanoate (esterification catalyst): 0.5 parts by mass The above materials were weighed and placed in a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. Next, the atmosphere in the flask was replaced with nitrogen gas, and the temperature was gradually raised with stirring, and the reaction was carried out for 2 hours at a temperature of 200°C with stirring.
[0081] The pressure in the reactor was then reduced to 8.3 kPa and maintained for 1 hour, after which it was cooled to 180 and returned to atmospheric pressure. Trimellitic anhydride: 6.5 parts by mass (0.03 moles; 20.0 mol% based on the total number of moles of polycarboxylic acids) tert-Butylcatechol (polymerization inhibitor): 0.1 parts by mass Thereafter, the above materials were added, the pressure in the reaction tank was reduced to 8.3 kPa, and the reaction was carried out for 12 hours while maintaining the temperature at 160°C. After it was confirmed that the softening point measured according to ASTM D36-86 reached 132°C, the temperature was reduced to stop the reaction, and binder resin H was obtained.
[0082] <Production of Pigment Dispersion 1> Pigment 35.0 parts by weight (Magenta pigment: Pigment Red 122) Binder resin L 65.0 parts by weight UFB water 3 5.0 parts by mass The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 20 s. -1After mixing for 5 minutes, the mixture was kneaded at 120°C in a twin-screw kneader (PCM-30, Ikegai Corporation) (Step 1). The resulting kneaded mixture was cooled and coarsely pulverized in a pin mill to a weight average particle size of 100 μm or less to obtain coarsely pulverized pigment dispersion 1. The melt viscosity of binder resin L at 120°C was 2080 Pa sec.
[0083] <Preparation of Pigment Dispersions 2 to 9 and Comparative Pigment Dispersions 1 to 6> Pigment Dispersions 2 to 9 and Comparative Pigment Dispersions 1 to 6 were obtained in the same manner as for Pigment Dispersion 1, except that the type and amount of UFB water were changed as shown in Table 2. [Table 2] In the table, the number of parts is by mass. "Parts relative to raw materials" indicates the number of parts by mass relative to 100.0 parts by mass of the binder resin and the dispersed substance in total.
[0084] <Production of finely pulverized material 1> Binder resin L 41.0 parts by weight Binder resin H 20.0 parts by weight Pigment dispersion 1 30.0 parts by weight Synthetic wax 1 (Hydrocarbon wax, maximum endothermic peak temperature 90°C) 9.0 parts by mass ·UFB water 1 5.0 parts by mass The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 20 s. -1 After mixing for 5 minutes, the mixture was kneaded in a twin-screw kneader (PCM-30 type, manufactured by Ikegai Corporation) (step 2). The kneaded mixture was cooled and coarsely pulverized in a pin mill to a weight average particle size of 100 μm or less to obtain coarsely pulverized product 1.
[0085] The obtained coarsely crushed material 1 was crushed in a mechanical crusher (Turbo Mill T250-CRS, rotor shape RS type, manufactured by Turbo Kogyo Co., Ltd.) shown in FIG. 1 under the following conditions: feed rate of 30 kg / h, rotor speed of 150 m / s, rotor-stator gap of 1.0 mm, cold air temperature of -10°C, and cold air volume of 10 m 3 Finely ground product 1 was obtained by grinding at 0.05 U / min.
[0086] <Production of Toner 1> The finely ground material 1 is classified using an air classifier that utilizes the Coanda effect ("Elbow Jet Lab EJ-L3", manufactured by Nittetsu Mining Co., Ltd.) by adjusting various conditions such as the injection air volume so as to obtain the target particle size and particle size distribution, and fine and coarse powders are simultaneously removed to produce toner particles. obtained. 100 parts by mass of the obtained toner particles were mixed with a toner having a specific surface area of 200 m2 measured by the BET method. 2 1.8 parts by mass of silica fine particles that had been hydrophobized with silicone oil were added, and the mixture was mixed in a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 30 s. -1 The mixture was mixed at 100° C. for a rotation time of 10 minutes to obtain toner 1. Toner 1 had a weight average particle size (D4) of 5.5 μm.
[0087] <Production of Toners 2 to 15 and Comparative Toners 1 to 7> In the production of toner 1, except that the types and parts of materials such as binder resin and pigment dispersion added were changed as shown in Table 3, finely pulverized materials 2 to 15 and comparative finely pulverized materials 1 to 7 were obtained in the same manner as in the production examples of finely pulverized material 1 and toner 1, and further classification was performed to obtain toners 2 to 15 and comparative toners 1 to 7. As shown in Table 3, in toners 5 to 14 and comparative toners 1 to 6, a binder resin and a pigment were used instead of a pigment dispersion.
[0088] [Table 3] In the table, the number of parts is by mass. "Parts relative to raw materials" indicates the number of parts by mass relative to 100.0 parts by mass of the binder resin and the dispersed substance in total.
[0089] <Magnetic Carrier 1 Manufacturing Example> Number average particle size: 0.30μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 1 Number average particle size: 0.50μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 2 To 100 parts of each of the above materials, 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added, and the mixture was mixed and stirred at high speed in a container at 100° C. or higher to treat each of the fine particles.
[0090] Phenol: 10% by weight Formaldehyde solution: 6% by mass (40% by mass of formaldehyde, 10% by mass of methanol, 50% by mass of water) Magnetite treated with the above silane compound 1: 58% by mass Magnetite 2 treated with the above silane compound: 26% by mass 100 parts of the above material, 5 parts of 28% by mass aqueous ammonia, and 20 parts of water were placed in a flask, and the temperature was raised to 85°C in 30 minutes and held while stirring and mixing, and polymerization reaction was carried out for 3 hours to harden the resulting phenolic resin. The hardened phenolic resin was then cooled to 30°C, and water was added, after which the supernatant liquid was removed, and the precipitate was washed with water and then air-dried. This was then dried at a temperature of 60°C under reduced pressure (5 mmHg or less) to obtain a spherical magnetic carrier 1 with magnetic material dispersion. The 50% particle size (D50) based on volume of the magnetic carrier 1 was 34.2 μm.
[0091] <Production example of two-component developer 1> Toner 1 (8.0 parts) was added to magnetic carrier 1 (92.0 parts), and mixed in a V-type mixer (V-20, manufactured by Seishin Enterprises) to obtain two-component developer 1.
[0092] <Production Examples of Two-Component Developers 2 to 15 and Comparative Two-Component Developers 1 to 7> In the production example of two-component developer 1, the same operation was carried out except that the combinations were changed to toners 2 to 15 and comparative toners 1 to 7, respectively, to obtain two-component developers 2 to 15 and comparative two-component developers 1 to 7.
[0093] Example 1: Evaluation of pigment dispersion Using Pigment Dispersions 1 to 9 (Example 1) and Comparative Pigment Dispersions 1 to 7 (Comparative Example 1), the amount of coarse pigment particles was evaluated by the following method.
[0094] <Method for evaluating pigment dispersibility of pigment dispersion> A thin film of the pigment dispersion was prepared, and the coarse particles of the pigment were observed using an optical microscope, and then the number of coarse particles was counted for evaluation. First, 30 mg of the pigment dispersion was weighed out and placed in a powder molding die DD3015-0810 (NPa Systems Co., Ltd.), and pressed at a pressure of 20 MPa for 20 seconds using a small heat press machine (HC300-15, AS ONE Co., Ltd.) to prepare pellets of the pigment dispersion. Next, the pellets were placed on an OHP film (VF-1420N, Kokuyo Co., Ltd.), a Naflon tape (TOMBO9001, Nichias Co., Ltd.) was placed on top of the pellets, and the pellets were then set in a small heat press. After preheating at 150°C for 1 minute and 30 seconds, the pellets were pressed at 10 MPa for 1 minute. This produced a thin film of the pigment dispersion.
[0095] When the prepared thin film of the pigment dispersion was observed with an optical microscope (VHX-5000, Keyence), elliptical pigment aggregates of several μm to 100 μm were observed to be darker than the background color. An image of the pigment dispersion thin film was obtained with a field of view of 1.6 mm × 1.2 mm at a magnification of 300 times using an optical microscope. The number of coarse pigment particles of 2 μm or more observed in the obtained image was counted as the pigment dispersion index using image processing software ImageJ, and the result was evaluated according to the following criteria. The evaluation results are shown in Table 4. (Evaluation Criteria) A: The number of coarse pigment particles is less than 150 B: Number of coarse pigment particles: 150 or more and less than 200 C: Number of coarse pigment particles: 200 or more and less than 250 D: Number of coarse pigment particles: 250 or more and less than 300 E: Number of coarse pigment particles: 300 or more
[0096] [Table 4]
[0097] Example 2: Evaluation of toner Grindability evaluation was performed for Toners 1 to 15 and Comparative Toners 1 to 7, and coloring power evaluation was performed for Toners 1 to 15 and Comparative Toners 1 to 7.
[0098] <Evaluation of toner grindability> The smaller the particle size of the finely pulverized material produced by the same pulverizing means, the better the pulverizability during toner production. The weight average particle size (D4) of each finely pulverized material before obtaining the above-mentioned Toners 1 to 15 and Comparative Toners 1 to 7 was measured using the above-mentioned measuring method, and the particle size distribution of the finely pulverized materials 1 to 15 and Comparative Finely pulverized materials 1 to 7 was obtained. Evaluation was performed based on the weight average particle size (D4) according to the following criteria. The evaluation results are shown in Table 5. <Evaluation criteria> A: Weight average particle size (D4) is less than 5.20 μm B: Weight average particle size (D4) is 5.20 μm or more and less than 5.40 μm C: Weight average particle size (D4) is 5.40 μm or more and less than 5.60 μm D: Weight average particle diameter (D4) is 5.60μm or more
[0099] <Method for evaluating toner coloring power> As the image forming apparatus, a Canon full-color copying machine imageRUNNER ADVANCE C5255 was used, and the evaluation was performed by putting two-component developer 1 into the developing device of the magenta station. The evaluation environment was normal temperature and humidity (23°C, 50% RH), and the evaluation paper was plain copy paper CS-068 (A4 paper, basis weight: 68 g / m 2 (sold by Canon Marketing Japan Inc.) was used. First, in the evaluation environment, an image was output with a constant developing bias, and the image density of the output image was examined. The image density was measured using an X-Rite color reflection densitometer (500 series: manufactured by X-Rite Corporation). Based on the results of the X-Rite color reflection densitometer, the coloring power of two-component developer 1 using toner 1 was evaluated according to the following criteria. Similarly, images were output using two-component developers 2 to 15 and comparative toners 1 to 7, respectively, and the coloring power was evaluated according to the following criteria based on the measured image density. (Evaluation Criteria) A: Image density 1.85 or higher B: Image density 1.75 or more and less than 1.85 C: Image density 1.65 or more and less than 1.75 D: Image density 1.55 or more and less than 1.65 E: Image density less than 1.55
[0100] [Table 5]
[0101] The present disclosure relates to the following methods. (Method 1) A method for producing a toner, comprising the steps of: The method for producing the toner includes the steps of: The method includes a melt-kneading step of melt-kneading a mixture A containing a binder resin and a substance to be dispersed in the binder resin to obtain a kneaded product, the mixture A contains 1.0 to 10.0 parts by mass of water relative to 100.0 parts by mass of the binder resin and the dispersed substance in total, The water contained in the mixture A contains bubbles including ultrafine bubbles having a particle diameter of 1000 nm or less, The water contained in the mixture A has ultra-fine bubbles of 1.0×10 4 5. A method for producing a toner comprising the steps of: (Method 2) The method for producing a toner according to method 1, further comprising a step of pulverizing the kneaded mixture. (Method 3) 3. The toner producing method according to method 1 or 2, wherein the material to be dispersed contains a release agent. (Method 4) 3. The toner producing method according to method 1 or 2, wherein the dispersed material contains a pigment. (Method 5) The toner producing method according to the method 1 or 2, wherein the dispersed material contains a pigment and a release agent. (Method 6) The toner producing method according to any one of Methods 1 to 5, wherein the mixture A contains 2.0 to 8.0 parts by mass of the water with respect to a total of 100.0 parts by mass of the binder resin and the dispersed substance. (Method 7) The toner producing method according to any one of Methods 1 to 6, wherein the number average particle diameter of the bubbles is 1000 nm or less. (Method 8) The toner producing method according to any one of Methods 1 to 7, wherein the number average particle diameter of the bubbles is 700 nm or less. (Method 9) the melt-kneading step is a first melt-kneading step of melt-kneading a first mixture containing a part of the binder resin and at least a part of the pigment to obtain a first kneaded product, The first mixture is mixture A, The toner producing method according to Method 4 or 5, further comprising, after the first melt-kneading step, a second melt-kneading step of melt-kneading a second mixture containing at least the first kneaded mixture and the remaining binder resin. (Method 10) the second mixture contains 1.0 to 10.0 parts by mass of water with respect to a total of 100.0 parts by mass of the binder resin and the dispersed substance in the second mixture, The water contained in the second mixture contains bubbles including ultrafine bubbles having a particle diameter of 1000 nm or less, The water contained in the second mixture has ultra-fine bubbles of 1.0×10 4 10. A method for producing a toner according to claim 9, wherein the toner contains more than 1000 particles / mL. [Explanation of symbols]
[0102] 101: powder supply port, 102: volute, 103: rotor, 104: stator, 105: rear chamber, 106: powder discharge port, 107: rotating shaft, 108: cold air generator, 109: cold water supply port, 110: cold water discharge port
Claims
1. A method for producing a toner, comprising the steps of: The method for producing the toner includes the steps of: The method includes a melt-kneading step of melt-kneading a mixture A containing a binder resin and a substance to be dispersed in the binder resin to obtain a kneaded product, the mixture A contains 1.0 to 10.0 parts by mass of water per 100.0 parts by mass of the binder resin and the dispersed substance in total, The water contained in the mixture A contains bubbles including ultrafine bubbles having a particle diameter of 1000 nm or less, The water contained in the mixture A has ultra-fine bubbles of 1.0×10 4 3. A toner manufacturing method according to claim 1, wherein the toner contains more than 100 particles / mL.
2. The method for producing a toner according to claim 1 , further comprising a step of pulverizing the kneaded mixture.
3. The method for producing a toner according to claim 1 or 2, wherein the dispersion medium contains a release agent.
4. The method for producing a toner according to claim 1 or 2, wherein the dispersed material contains a pigment.
5. The method for producing a toner according to claim 1 or 2, wherein the dispersed material contains a pigment and a release agent.
6. 3. The method for producing a toner according to claim 1, wherein the mixture A contains 2.0 to 8.0 parts by mass of the water with respect to a total of 100.0 parts by mass of the binder resin and the dispersed substance.
7. The method for producing a toner according to claim 1 , wherein the number average particle diameter of the bubbles is 1000 nm or less.
8. The method for producing a toner according to claim 1 , wherein the number average particle diameter of the air bubbles is 700 nm or less.
9. the melt-kneading step is a first melt-kneading step of melt-kneading a first mixture containing a part of the binder resin and at least a part of the pigment to obtain a first kneaded product, The first mixture is mixture A, The method for producing a toner according to claim 4 , further comprising, after the first melt-kneading step, a second melt-kneading step of melt-kneading a second mixture containing at least the first kneaded product and the remaining binder resin.
10. the second mixture contains 1.0 to 10.0 parts by mass of water with respect to a total of 100.0 parts by mass of the binder resin and the dispersed substance in the second mixture, The water contained in the second mixture contains bubbles including ultrafine bubbles having a particle diameter of 1000 nm or less, The water contained in the second mixture has ultra-fine bubbles of 1.0×10 4 The method for producing a toner according to claim 9 , wherein the toner contains at least one of the above-mentioned components / mL.
Citation Information
Patent Citations
Toner and method for manufacturing toner
JP2002072554A
Toner, its making method, developer, and method and apparatus for forming image
JP2003098739A
Method of manufacturing color toner and color toner
JP2005352131A
Electrophotographic toner
JP2008191491A
Toner and manufacturing method of the same
JP2015132645A